ANALISA PENDAPATAN PETERNAKAN AYAM BROILER POLA KEMITRAAN DI MARIOTO FARM KABUPATEN BLITAR - Rochim, Achmad Abdul Rochim; samur, Salnan Irba Novaela Samur; widyasworo, Agustina (Universitas Islam Balitar, 2024)
Broiler chicken farming is a business that is easy for everyone to run. Independent broiler chicken farming businesses often face higher risks, one of the factors being the selling price which tends to be below the cost of goods sold, so farmers often experience losses. Partnership pattern broiler chicken farming is a way to reduce existing risks. Income is one of the important references for breeders to continue their partnership business. The general public must know the income earned by breeders from partnership farming businesses. Research conducted at Marioto Farm used descriptive quantitative methods by describing the results of farmers' income during six production periods. The results of the research obtained show that the total production costs were IDR 510,809,226. Meanwhile, the revenue obtained during the six production periods by partnering with partnerships was IDR 550,484,370. The income received by farmers while running a partnership system livestock business is IDR 41,626,545. The income obtained is income for six production periods. The R/C ratio value obtained shows a result of 1.08, indicating that this livestock business is suitable to be continued. The production BEP obtained during the six production periods was 22,496 kg and the BEP price was IDR 21,031. The conclusion of this research is that the income of farmers by partnering with partnerships earns a total income of IDR 41,626,545. This is quite a large amount for home scale farming. The livestock business in partnership deserves to be continued again